2019
DOI: 10.1016/j.engappai.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial Multi Agent System for real-time distributed collaborative prognostics

Abstract: Despite increasing interest, real-time prognostics (failure prediction) is still not widespread in industry due to the difficulties of existing systems to adapt to the dynamic and heterogeneous properties of real asset fleets. In order to address this, we present an Industrial Multi Agent System for real-time distributed collaborative prognostics. Our system fulfils all six core properties of Advanced Multi Agent Systems: Distribution, Flexibility, Adaptability, Scalability, Leanness, and Resilience. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Yong et al have proposed an architecture that can be used to take the various sources of uncertainty, including the sensors’ measurement uncertainty, into account in the predictions. Salvador Palau et al have presented an advanced multi-agent system for real-time distributed collaborative prognostics [ 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…Yong et al have proposed an architecture that can be used to take the various sources of uncertainty, including the sensors’ measurement uncertainty, into account in the predictions. Salvador Palau et al have presented an advanced multi-agent system for real-time distributed collaborative prognostics [ 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…As a result, any given asset's data repository is enriched with failure trajectories originating from other assets. Prediction models are then trained using the enriched dataset [9]. Other such similarity‐based prognoses have also been proposed by researchers [12–14].…”
Section: Introductionmentioning
confidence: 99%
“…However, an industrial system of assets is often characterised by widespread heterogeneity, due to assets operating in varied conditions, model types, and the presence of multiple failure modes. It has been shown that in such settings, it is beneficial to have separate prediction models catering to subsets of asset populations, identified based on some sense of homogeneity [7, 9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations